Implementation of The Educational Mobile Application (AME) in The PHBS Program At The Al-Itqon Islamic Boarding School In Semarang, Indonesia - Lisdiana, Lisdiana; Putra, Ngurah Made Dharna; Hartadiyati WH, Eny; Nuraini, Liya Aliyah; Amala, Khilya Mufrida; Shalsabila, Fitria (Universitas Negeri Semarang, 2025)
Education and implementation of Clean and Healthy Living Behaviors (PHBS) are essential to enhance awareness and hygiene practices within Boarding School environments. PHBS education encompasses personal hygiene, waste management, use of sanitation facilities, and healthy eating habits. This community activity aims to improve students' awareness of the importance of healthy lifestyle behaviors using an educational mobile application (AME). The activity will take place from June 18, 2025, to July 18, 2025, at the Al-Tqon Bugen Islamic Boarding School in Semarang. The community service activity includes preparation, socialization, implementation, monitoring, and evaluation. In the learning process, a technology-based educational approach with gamification is used, which integrates game elements into the educational process using digital technology, packaged in the AME. The results of the activity show that 86% of students are categorized as moderate to high in terms of increased use of digital technology. The results of this activity can be concluded that AME technology in the implementation of PHBS can function as an effective strategy to encourage students to maintain personal hygiene and environmental cleanliness.